Economic Violence Against Women: A Case of Mental Health Perspective - Setiawati, Ririn; Marhumah, Marhumah; Lessy, Zulkipli (PALASTREN: Jurnal Studi Gender, 2022)
As a group who are considered weak, it is not surprising that the cases of violence against women tend to happen repeatedly in Indonesia. Although there are a plethora of violence such as physical violence, psychological violence, sexual violence, and economic violence, these days physical violence remains the number one case in society. Generally economic violence is completely an invisible form of violence in society. This is essentially deemed a small matter, in which one of the causes is the concept of authoritarianism embedded in society. This study aims to investigate the forms of economic violence frequently experienced by women and its impact on women’s mental health. A qualitative method was employed with a case study approach. A purposive sampling was presented in this study with the sample consisting of two people. The findings showed that there are several varieties of economic violence against women such as inhibiting the development of women’s career, taking women’s financial well-being without permission, controlling family assets strictly, and obligating women to create a financial report. In addition, this violence has a significant deteriorating effect on women's mental health including frustration, conflict, fright, stress, and threats. As the last point, it was found that there is a relevance between economic violence and other types of violence